SHM_415292_HST_3D Flint Platform Core - Qallaki, Ylber; Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Late Mesolithic flint platform core from Sweden, currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=697

Link to Sök I Samlingarna

https://samlingar.shm.se/object/A1438A33-5105-4ADC-AE32-CE0FEAD0FADC
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Late Mesolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi